Seasonal fluctuation of some limnological variables on a floodplain lake (Patos lagoon) of the Upper Paraná River, Mato Grosso do Sul State, Brazil - Rodrigues Luzia Cleide; Train Sueli; Roberto Maria do Carmo; Pagioro Thomaz Aurélio (Brazilian Archives of Biology and Technology, 2002)
Temporal variations of some limnological variables in limnetic and littoral regions of Patos lagoon, a "várzea" lake on the floodplain of the Upper Paraná River (22(0) 43'12"S e 53(0) 17'37"W), were studied in relation to hydrological and climatological factors. Measurements of water temperature, euphotic zone, suspended material, electrical conductivity, total alkalinity, pH, dissolved oxygen, carbon dioxide, total nitrogen, total Kjeldahl nitrogen, total phosphorus, dissolved phosphorus, reactive soluble phosphorus and chlorophyll a were taken monthly between March 1993 and February 1994. Results lend evidence to the importance of the hydrological regime on the dynamic of limnological variables in floodplain lakes. A dilution of nutrients in the lagoon, especially phosphates, occurred during floods. This was followed by fertilization of the environment by nutrients from the inundated marginal regions. During low connectivity periods, autochthonous, events such as ressuspension of sediment, brought on by wind and rain, governed limnological events in the lagoon.